Nghiên cứu về giáo dục kĩ năng định hướng và di chuyển cho trẻ khiếm thị đa tật - Nguyễn, Thị Hằng; Trần, Thị Văng; Phạm, Thị Trang (Tạp chí Giáo dục, 2024)
Visual impairments in blind children in general and children with multiple disabilities and blindness in particular severely affect their learning, playing, daily activities and community integration. One of the core skills for children with visual impairment and multiple disabilities to be independent and autonomous is the ability to move independently. Guidance and transfer are the foundation for learning because as children continue to explore the world around them, learning will take place. Therefore, educating children with visual impairment and multiple disabilities to move independently and autonomously in different environments is the key to ensuring the success of inclusive education. This article reviews the concept of children with visual impairment and multiple disabilities, the concept of orientation and mobility, introduces assessments and measurements of orientation and mobility skills and proposes the basic contents of the Orientation and Mobility Skills Education program for children with visual impairment and multiple disabilities.